Maternal dietary glycemic index and glycemic load in early pregnancy are associated with offspring adiposity in childhood: the Southampton Women's Survey. - Okubo, H; Crozier, SR; Harvey, N; Godfrey, K; Inskip, H; Cooper, C; Robinson, S (American Society for Nutrition, 2014)
BACKGROUND: Maternal hyperglycemia in pregnancy is associated with greater adiposity in offspring. The glycemic index (GI) and glycemic load (GL) describe the glycemic response to carbohydrate ingestion. However, the influence of maternal dietary GI and GL in pregnancy on childhood adiposity is unknown.OBJECTIVE: We examined relations of maternal dietary GI and GL in early and late pregnancy with offspring body composition.DESIGN: A total of 906 mother-child pairs from the prospective cohort the Southampton Women's Survey were included. Children underwent dual-energy X-ray absorptiometry measurements of body composition at birth and 4 and 6 y of age. Log-transformed fat mass and lean mass were standardized with a mean (±SD) of 0 ± 1. Maternal dietary GI and GL were assessed at 11 and 34 wk of gestation by using an administered food-frequency questionnaire.RESULTS: After control for potential confounders, both maternal dietary GI and GL in early pregnancy were positively associated with fat mass at 4 and 6 y of age [fat mass SDs per 10-unit GI increase: β = 0.43 (95% CI: 0.06, 0.80), P = 0.02 at 4 y of age; β = 0.40 (95% CI: 0.10, 0.70), P = 0.01 at 6 y of age; fat mass SDs per 50-unit GL increase: β = 0.43 (95% CI: 0.19, 0.67), P < 0.001 at 4 y of age; β = 0.27 (95% CI: 0.07, 0.47), P = 0.007 at 6 y of age]. In contrast, there were no associations between maternal dietary GI or GL in late pregnancy and offspring fat mass at these ages. Maternal dietary GI and GL were not associated with fat mass at birth or offspring lean mass at any of the ages studied.CONCLUSION: Higher maternal dietary GI and GL in early pregnancy are associated with greater adiposity in childhood.